17‐3: Towards Flexible Glass: Ultra‐Thin Glass with Tight Dimensional Tolerance and High Strength Achieved by Ion Exchange. Issue 1 (2nd June 2017) - He, Feng; Jotz, Matthias; Wegener, Holger; Hahn, Michael; Da, Ning; Zimmer, Jose
Abstract : Ultrathin aluminosilicate glass AS 87 eco, has been produced by SCHOTT proprietary downdraw hot‐forming method as thin as 50 μm. A tight thickness tolerance of ± 10um, with a TTV <10 um across an area of 400×500mm, and a surface roughness smaller than 1 nm have been achieved in mass production. Compared with other ultrathin glass, the uniqueness of AS 87 eco lies in its the outstanding chemical strengthening performance, where the surface compressive stress can reach over 800 MPa after an ion‐exchange process in molten KNO3 salt bath. The high alumina content also accelerates the Na‐K diffusion, and an ion exchange depth of 20 μm can be achieved after toughening at 390C for 2h. Combining such chemical strengthening with fine edge treatment results in an extremely high bending strength over 1GPa, allowing a safe bending radius as low as 3mm for 70 μm thick glass. As such, this ultrathin glass enables a highly scratch‐resistant glass cover for applications such as foldable displays and any other applications requiring the combined properties of strength, transparency, flexibility, and scratch‐resistance properties. Low breakage strength is the most significant obstacle for a wide application of ultrathin glass, and aluminosilicate glass can be strengthened well after ion exchange. SCHOTT is the first supplier in mass production of directly hot‐formed ultrathin aluminosilicate glass eliminating the need for chemical thinning.